Water Withdrawals and Their Use in Florida in 2010 - Tatiana Borisova; Jenna Rogers (EDIS)
This publication is based on Florida water use information collected by the United States Geological Service. It expands on EDIS document FE797 that examined Florida water withdrawals data for 2005. In addition, in EDIS document FE757 (Florida’s Water Resources), the authors describe Florida’s abundant water resources—the state receives about 54 inches of rainfall per annum, compared to 30 inches nationwide, and it overlies prolific aquifers. Whether water is scarce or abundant, however, depends not only upon available supplies, but also upon patterns of water use. To gather this information, the United States Geological Survey employs several water-use categories to develop estimates of water withdrawals and water use. This 5-page fact sheet was written by Tatiana Borisova and Jenna Rogers, and published by the UF Department of Food and Resource Economics, May 2014.